Fatigue in systemic lupus erythematosus Association with disease activity, quality of life and psychosocial factors - ALİBAZ ÖNER, FATMA; MUMCU, GONCA; DİRESKENELİ, RAFİ HANER; TUĞLULAR, ZÜBEYDE SERHAN (SPRINGER HEIDELBERG, 2017)
Objective. The aim of the study was to determine which disease-related factors and non-disease features can explain the presence of systemic lupus erythematosus (SLE)-related fatigue in Turkish patients. Methods. This cross-sectional study was carried out with 99 SLE patients and 71 healthy controls. To assess fatigue and health-related quality of life (HRQoL) the participants were asked to complete two questionnaires: the short form-36 health survey (SF-36) and the multidimensional assessment of fatigue (MAF) scale. Anxiety and depression of participants were assessed by the hospital anxiety and depression scale (HADS). Results. A total of 99 patients (female/male 95/4) and 71 controls (female/male 40/31) were studied. The mean age and standard deviation (+/- SD) of patients and controls were 43.3 +/- 12.2 years and 43.2 +/- 12.1 years, respectively. The mean (SD) disease duration was 7.8 +/- 5.3 years and median SLE disease activity index (SLEDAI) score was 0 (range = 0-16). The level of fatigue was higher in patients compared to controls with mean MAF scores of 24.7 +/- 12.2 and 12.8 +/- 9.9 (p < 0.001), respectively. The HADS-D and HADS-A scores were also significantly higher in SLE patients (6.6 +/- 4.3 vs. 3.6 +/- 2.9, p < 0.001 and 7.2 +/- 4 vs. 4.9 +/- 4, p = 0.007, respectively). There were no significant associations between the MAF and SLEDAI scores (r = 0.05, p = 0.63) but MAF scores positively correlated with age, HADS-A and HADS-D scores and negatively correlated with physical component summary (PCS), mental component summary (MCS) and each domain of SF-36 except role emotional in SLE patients. Conclusion. Fatigue is an important factor influencing patient daily life independent from disease activity in our study. The SLE patients with severe fatigue should also be assessed for other possible underlying causes such as anxiety, depression and poor quality of life.
Keywords: Systemic lupus erythematosus; Fatigue; Quality of life; Anxiety; Depression; RHEUMATOID-ARTHRITIS; REPORTED FATIGUE; SEVERITY SCALE; UNMET NEEDS; DEPRESSION; PREVALENCE; SWEDISH; ANXIETY; PEOPLE; ADULTS